Measuring the Capital Adequacy Ratio for Bank Business Activity Group 3 that listed in Indonesia Stock Exchange - Herlina*, Listri; Suryaningprang, Andre (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This study analyzes how the capital condition of 10 commercial banks in the category of bank business activity group 3 which is listed on IDX. The analysis is related to central bank regulation concerning banks being required to increase capital more than the minimum capital adequacy ratio as a buffer to prevent a crisis. Using the panel data regression method to analyze the issue, four independent variables used from internal factors namely Non-Performing Loan, Net Interest Margin, Loan to Deposit Ratio, and Credit Growth, there are one bank has the capital highest and only needs to increase its capital for 4% to join bank business activity group. Furthermore, there are three banks with the lowest capital adequacy ratio. Research results found that NPL significantly affects the capital of 10 banks Group 3. Based on the result, when Non-Performing Loans increase the banks will increase their capital reserves beyond the minimum capital reserves that have been set as a buffer against potential losses. Keywords: CAR; Bank Capital; Fixed Effect Method; Buffer; NPL Abstrak Penelitian ini dilakukan untuk mengetahui bagaimana kondisi permodalan 10 bank umum dalam kategori kegiatan usaha bank kelompok 3 yang terdaftar di BEI. Analisis ini terkait dengan peraturan bank sentral tentang bank yang wajib meningkatkan modal lebih dari rasio kecukupan modal minimum sebagai penyangga (Buffer) apabila terjadi krisis keuangan dan ekonomi yang dapat mengganggu stabilitas sistem keuangan. Dengan menggunakan metode regresi data panel untuk menganalisis permasalahan tersebut, digunakan empat variabel independen dari faktor internal yaitu NPL, NIM, LDR, Pertumbuhan Kredit. Terdapat 1 bank yang memiliki permodalan tertinggi dan dengan hanya menambah modal sebesar 4% bank tersebut dapat masuk kedalam kategori Bank Unit Kegiatan Usaha. Selanjutnya, terdapat tiga bank dengan rasio kecukupan modal terendah sehingga bank tersebut wajib meningkatkan modalnya. Hasil penelitian membuktikan bahwa NPL berpengaruh positif dan signifikan terhadap permodalan 10 bank Bank Unit Kegiatan Usaha 3. Dengan berpengaruhnya NPL terhadap permodalan bank, maka Ketika NPL meningkat bank akan menambah cadangan modal melebihi minimum cadangan modal yang telah di tetapkan sebagai penyangga terhadap potensi kerugian. Kata Kunci: CAR; Modal bank; Metode Fixed Effect; Penyangga; NPL